Advancing Program Theory for Licensed Assisted Living Services in Independent Housing. Issue 3 (3rd July 2019) - Greenfield, Emily A.
Abstract: Assisted living programs (ALPs) embed licensed assisted living services within independent housing. To advance nascent research on this type of housing plus services, this study aimed to develop empirically grounded program theory on the processes through which ALPs benefit residents within independent housing. Eighteen in-depth interviews were conducted with current and prospective consumers of an ALP in northern New Jersey, including residents and family caregivers. The setting for the ALP was a federally subsidized independent housing building, which had introduced the ALP approximately 1 year prior to the study. Themes emerging from an iterative coding process indicated the most valued aspects of the ALP's service delivery, including the comprehensiveness of the service options, the flexible timing for their delivery, and the relational aspects of care. Participants further described the ways in which the structure of the ALP facilitated prevention, such as preventing the occurrence and escalation of adverse health events. The study concludes by presenting a program model that integrates these findings, which suggests that ALPs deliver care in ways that make long-term services and supports more accommodating and acceptable to consumers. This, in turn, can enhance their preventive value to facilitate aging in place among independent housing residents in clinical need of such supports.